Moisture availability limits subalpine tree establishment. Issue 3 (22nd February 2018) - Andrus, Robert A.; Harvey, Brian J.; Rodman, Kyle C.; Hart, Sarah J.; Veblen, Thomas T.
Abstract: In the absence of broad‐scale disturbance, many temperate coniferous forests experience successful seedling establishment only when abundant seed production coincides with favorable climate. Identifying the frequency of past establishment events and the climate conditions favorable for seedling establishment is essential to understanding how climate warming could affect the frequency of future tree establishment events and therefore future forest composition or even persistence of a forest cover. In the southern Rocky Mountains, USA, research on the sensitivity of establishment of Engelmann spruce ( Picea e ngelmannii ) and subalpine fir ( Abies lasiocarpa )—two widely distributed, co‐occurring conifers in North America—to climate variability has focused on the alpine treeline ecotone, leaving uncertainty about the sensitivity of these species across much of their elevation distribution. We compared annual germination dates for >450 Engelmann spruce and >500 subalpine fir seedlings collected across a complex topographic‐moisture gradient to climate variability in the Colorado Front Range. We found that Engelmann spruce and subalpine fir established episodically with strong synchrony in establishment events across the study area. Broad‐scale establishment events occurred in years of high soil moisture availability, which were characterized by above‐average snowpack and/or cool and wet summer climatic conditions. In the recent half of the study period (1975–2010), a decrease in the number of fir and spruce establishment events across their distribution coincided with declining snowpack and a multi‐decadal trend of rising summer temperature and increasing moisture deficits. Counter to expected and observed increases in tree establishment with climate warming in maritime subalpine forests, our results show that recruitment declines will likely occur across the core of moisture‐limited subalpine tree ranges as warming drives increased moisture deficits.